PROVIDING HOUSING TO THE INDIGENOUS PEOPLE OF ORANG LAUT: Fulfilling Rights or Changing Culture? - Tan, Winsherly; Kalita, Manashi; Seroja, Triana Dewi; Nurlaily, Nurlaily; Silviani, Ninne Zahara (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
The right to get a decent place to live is the right of every person, including the sea people. Therefore, the local government builds houses and moves the sea people from living on boats and nomads to houses. The problem is that living in a house has changed their culture, which usually lives a nomadic life at sea. The purpose of this study is first to analyze the accuracy of the local government’s steps. Second, to analyze the right legal solution in providing decent housing for the sea people. The method in this study is empirical juridical. The type of data used is primary data, namely observations and interviews, and secondary data, namely laws and regulations. In addressing the formulation of the problem in this study, the legal and theoretical basis is the Progressive Legal Theory. The results of the study indicate that the steps taken by the local government in providing physical housing and legalizing the houses are good, but not right, because they have changed the culture of the sea people. A house is a manifestation of a group’s culture, so moving the sea people into houses not only changes their culture but also their lifestyle and work patterns. Therefore, the legal solution is to establish a halfway house with an empowerment program for the sea people, which can be regulated under the Lingga, Indonesia regional regulation. Then it is also necessary to form a law that specifically regulates indigenous peoples to accommodate the traditional rights of indigenous peoples.